Applications of High Pressure Technology in Food Processing - K. R. Jolvis Pou (International Journal of Food Studies)
Consumer trends towards shelf-stable, safe, more natural and free from additives foods drove the need to investigate the commercial application of non-thermal food processing technologies. High pressure processing (HPP) is one such emerging technology where foods are generally subjected to high pressure (100-1000 MPa), with or without heat. Similar to heat pasteurization, HPP deactivates pathogenic microorganisms and enzymes, extends shelf life, denatures proteins, and modifies structure and texture of foods. However, unlike thermal processing, HPP can retain the quality of fresh food products, with little or no impact on nutritional value and organoleptic properties. Moreover, HPP is independent of the geometry (shape and size) of food products. The retention of food quality attributes, whilst prolonging shelf life, are enormous benefits to both food manufacturers and consumers. Researches have indicated that the combination of HPP and other treatments, based on the hurdle technology concept, has potential synergistic effects. With further advancement of the technology and its large-scale commercialization, the cost and limitations of this technology will probably reduce in the near future. The current review focuses on the mechanism and system of HPP and its applications in the processing of fruit, vegetables, meat, milk, fish and seafood, and eggs and their derived products.